2009
DOI: 10.2478/s11687-009-0016-9
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary studies on the zoonotic importance of rodents as a reservoir of toxocariasis from recreation grounds in Wroclaw (Poland)

Abstract: 80 SummaryDue to their specific biology and behaviour, rodents could play a role as an intermediate, definitive or paratenic host for many helminth species, as well as for species of zoonotic significance such as Toxocara spp. or Echinococcus multilocularis. The aim of our preliminary study was to investigate the nematode fauna of rodents collected from recreation grounds located in the vicinity of Wroclaw, and to determine their role in the transmission of toxocariasis in this area. During a one-year period, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Even though the number of examined samples is not significant, it refers to the permanent circulation of toxocarosis in monitored habitats. Miterpáková et al (2009) determined 12.5 -13 % prevalence of T. canis in red foxes from localities where small rodents were trapped. Prevalence of larval toxocarosis in paratenic hosts was not found to be significantly influenced by the population age, however two times higher prevalence of infection in adults than in subadults suggests that probability of infection with roundworm eggs from contaminated environment increases with the exposure time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though the number of examined samples is not significant, it refers to the permanent circulation of toxocarosis in monitored habitats. Miterpáková et al (2009) determined 12.5 -13 % prevalence of T. canis in red foxes from localities where small rodents were trapped. Prevalence of larval toxocarosis in paratenic hosts was not found to be significantly influenced by the population age, however two times higher prevalence of infection in adults than in subadults suggests that probability of infection with roundworm eggs from contaminated environment increases with the exposure time.…”
Section: Discussionmentioning
confidence: 99%
“…larvae in four animals (12.9 %). The data refer to the role of rodents in the spread of toxocarosis in the suburban and tourist area (Hildebrand et al, 2009). In conclusion, the study highlights the important role of small rodents in permanent maintenance of the parasite particularly in alluvia, ecotones of forests and in agrocoenoses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of helminth species in A. agrarius from Belorussia was reported by Shimalov (2002) and the metazoan parasite fauna of A. flavicollis from Germany was described by Klimpel et al (2007a). Only Hildebrand et al (2009) have reported the nematode fauna of both the striped field mouse and the yellownecked mouse from Poland. In Slovakia, the helminth fauna of wild rodent species has been monitored for the last fifty years.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, such localities pose higher risk of exposure to E. multilocularis infection for humans. Rodents can transmit infectious agent also to domestic carnivores, facilitating transmission of the disease to man (Hildebrand et al, 2009). Therefore, preventive measures, for example anthelmintic bait distribution that decreases E. multilocularis prevalence in definitive hosts (Antolová et al, 2006;Romig et al, 2007), should be applied to reduce infection pressure on men in hyperendemic areas.…”
Section: Discussionmentioning
confidence: 99%